Employing Taguchi method to optimize the performance of a microscale combined heat and power system with Stirling engine and thermophotovoltaic array. (1st May 2023) - Chen, Wen-Lih; Currao, Gaetano; Li, Yueh-Heng; Kao, Chien-Chun
Abstract: This study proposes a biosyngas-fueled power system, which is a fusion between a micro-thermophotovoltaic (micro-TPV) system and a Stirling engine. The combustor in the micro-TPV is a coaxial tube made of platinum. Biosyngas was simulated using different compositions of H2 and CO mixture. The H2 /CO/air mixture was delivered to the inner channel of the micro-TPV combustor, while the CH4 /air mixture was delivered to the outer channel. This study realized a micro-CHP system with a combustion-driven TPV cell array, and a Stirling engine-driven power generation system. This micro-CHP system harvests energy generated through thermal radiation from the reactor's surface as well as thermal energy from hot flue gas. The results indicate that the overall efficiency of the biosyngas-fueled micro-CHP system was strongly dependent on fuel composition, fuel/air ratio, and flowrate mixture. Thus, Taguchi method was employed to find optimal operative conditions; the highest efficiency was achieved under a biosyngas composition of 80% CO and 20% H2, with a flow velocity of 6 ms −1, and an equivalence ratio of 1.2, and its corresponding overall efficiency reached 43%, incorporating 0.84 W electricity output by TPV cell array, 3.25 W electricity output by Striling engine-driven power generation system, and 325.5 W of water energy gained. Highlights: Biosyngas-fueled micro-CHP system features good fuel adaptability and reliability. The catalytic reactivity of micro TPV combustor extends system maneuverability. Taguchi method was employed to optimize the overall efficiency of Micro-CHP. Three optimal indicators were proposed and implemented in the Taguchi method. The overall efficiency of the micro-CHP system with optimal conditions reached 43%.